2023
DOI: 10.1002/crat.202300200
|View full text |Cite
|
Sign up to set email alerts
|

Study on Structures Stability, Mechanical Properties, and Electronic Properties of Alloy Ag–Au–Al: First‐Principles Calculations and Experiments

Xujin Han,
Manmen Liu,
Xiaolong Zhou

Abstract: In this paper, the silver–gold–aluminum alloy is prepared, and its effect on the microstructure and properties is observed by changing the content of aluminum. SEM observes the surface morphology, EDS (Energy Dispersive Spectrometer) detects the related tissue composition, and XRD (X‐ray Diffraction) verifies the composition. Ternary alloys are tested for hardness and resistivity. The results show that Ag‐15wt.%Au‐14wt.%Al alloy has the highest hardness. The resistivity test shows that Ag‐15wt.%Au‐18wt.%Al all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…The composition of the light region is Ag-69.60 at.% Al-27.05 at.% Au, which is likely to be the AuAl 2 phase [11]. Han et al also found a small shape with a light color with a phase composition atomic ratio Au to Al close to 1:2, which is determined as AuAl 2 [16]. The composition of the gray region is Ag-39.57 at.% Al-2.92 at.% Au, which is likely to be the Ag 2 Al phase [10].…”
Section: Phase Equilibria Of the Ag-al-au Ternary System At 450 • Cmentioning
confidence: 99%
“…The composition of the light region is Ag-69.60 at.% Al-27.05 at.% Au, which is likely to be the AuAl 2 phase [11]. Han et al also found a small shape with a light color with a phase composition atomic ratio Au to Al close to 1:2, which is determined as AuAl 2 [16]. The composition of the gray region is Ag-39.57 at.% Al-2.92 at.% Au, which is likely to be the Ag 2 Al phase [10].…”
Section: Phase Equilibria Of the Ag-al-au Ternary System At 450 • Cmentioning
confidence: 99%